Detection of microscopic filamentous fungal biofilms - Choosing the suitable methodology - Kulišová, Markéta; Maťátková, Olga; Brányik, Tomáš; Zelenka, Jaroslav; Drábová, Lucie; Kolouchová, Irena Jarošová (Journal of microbiological methods, 2023)
Microscopic filamentous fungi are ubiquitous microorganisms that adapt very easily to a variety of environmental conditions. Due to this adaptability, they can colonize a number of various surfaces where they are able to start forming biofilms. Life in the form of biofilms provides them with many benefits (increased resistance to desiccation, UV radiation, antimicrobial compounds, and host immune response). The aim of this study is to find a reliable and reproducible methodology to determine biofilm growth of selected microscopic filamentous fungi strains. Several methods (crystal violet staining, MTT assay, XTT assay, resazurin assay) for the determination of total biofilm biomass and its metabolic activity were tested on four fungi - Alternaria alternata, Aspergillus niger, Fusarium culmorum and Fusarium graminearum, and their biofilm was also imaged by spinning disc confocal microscopy using fluorescent dyes. A reproducible biofilm quantification method is essential for the subsequent testing of the biofilm growth suppression using antifungal agents or physical methods. Crystal violet staining was found to be a suitable method for the determination of total biofilm biomass of selected strains, and the MTT assay for the determination of metabolic activity of the biofilms. Calcofluor white and Nile red fluorescent stains successfully dyed the hyphae of microscopic fungi.
Keywords: houby; barvicí látky; Gentian Violet; Hyphae; Spinning disc confocal microscopy; biofilmy; Filamentous fungi; Tetrazolium salt assay; Biofilms; Antifungal Agents; genciánová violeť; hyfy; Fungi; Coloring Agents; Biofilm; antifungální látky; Crystal violet